Implementation of Good Corporate Governance Perspective: Case Study on Bumdes Samsam - Sari, Desak Made Mya Yudia (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2024)
The role of Village-Owned Enterprises (BUMDes) aims to realize village independence in managing their finances in increasing the economy and village income. BUMDes Samsam is one of the community organizations that performs well because it is able to provide remaining business results in accordance with the ratified household budget rules. BUMDes Samsam was formed from village funds which requires their financial reports to be in accordance with Permendagri Number 20 of 2018 concerning Village Financial Management. One thing that must be fulfilled is accountability for village financial management implementation activities. Accountability is often associated with Good Corporate Governance, including the financial activities of BUMDes. The research method used with case studies was proposed by Yin. Research was conducted at BUMDes Samsam on four informants who had direct contact with financial management accountability practices. Qualitative data was collected by observation, interviews and documentation. The research results are presented in narrative text. The research results show that the accountability of implementation applies the characteristics of participation, transparency, kinship, honesty, loyalty and integrity. This research can provide theoretical and practical implications that can influence village economic performance through BUMDes becoming independent villages